Effects of estrogen peripheral metabolism in rheumatoid arthritis - M. Cutolo; B. Villaggio; P. Montagna; S. Capellino (PAGEPress Publications, 2011)
It is well known that the immune reactivity is modulated by gender. In fact, women show a more effective immune response as well as a more frequent development of autoimmune diseases. In particular, 17b-estradiol (E2) in patients with systemic inflammatory diseases leads to an higher production of IgG and IgM in peripheral blood mononucleated cells (PBMC) and the secretion of metalloproteinases and IL-6 by synovial fibroblasts. The effect of E2 seems to be partially related to its concentration. In fact, at the physiological concentration, E2 seems to exert a pro-inflammatory effect, while at pharmacological concentrations shows anti-inflammatory effects. Steroid hormones can be converted in downstream hormones along defined pathways. The conversion of dehydroepiandrosterone (DHEA) in peripheral macrophages leads to the androgen production. Subsequently the enzyme aromatase converts androgens in estrogens, and its activity is increased by some inflammatory cytokines such as IL-1b, IL-6 and TNF-a. In the synovial fluids of rheumatoid arthritis (RA) patients the levels of estrogens result significantly increased compared with controls, showing the consequence of this unbalanced steroid metabolism. Furthermore, the metabolism of estrogens leads to some downstream hydroxylated metabolites, that are not waste products, but still active molecules in the inflammatory response. In fact, it has been found that synovial fluids of RA patients present a different ratio of 16-hydroxylated estrogen metabolites/ 2-hydroxylated metabolites, confirming that also the unbalanced metabolism of estrogens and not only the estrogen concentration seems to be related to the development and worsening of rheumatoid arthritis.